Rab GTPases Are Recruited to Chlamydial Inclusions in Both a Species-Dependent and Species-Independent Manner - Rzomp, Kimberly A. (American Society for Microbiology, 2003)
Chlamydiae are obligate intracellular bacteria that replicate within an inclusion that is trafficked to the peri-Golgi region where it fuses with exocytic vesicles. The host and chlamydial proteins that regulate the trafficking of the inclusion have not been identified. Since Rab GTPases are key regulators of membrane trafficking, we examined the intracellular localization of several green fluorescent protein (GFP)-tagged Rab GTPases in chlamydia-infected HeLa cells. GFP-Rab4 and GFP-Rab11, which function in receptor recycling, and GFP-Rab1, which functions in endoplasmic reticulum (ER)-to-Golgi trafficking, are recruited to Chlamydia trachomatis, Chlamydia muridarum, and Chlamydia pneumoniae inclusions, whereas GFP-Rab5, GFP-Rab7, and GFP-Rab9, markers of early and late endosomes, are not. In contrast, GFP-Rab6, which functions in Golgi-to-ER and endosome-to-Golgi trafficking, is associated with C. trachomatis inclusions but not with C. pneumoniae or C. muridarum inclusions, while the opposite was observed for the Golgi-localized GFP-Rab10. Colocalization studies between transferrin and GFP-Rab11 demonstrate that a portion of GFP-Rab11 that localizes to inclusions does not colocalize with transferrin, which suggests that GFP-Rab11's association with the inclusion is not mediated solely through Rab11's association with transferrin-containing recycling endosomes. Finally, GFP-Rab GTPases remain associated with the inclusion even after disassembly of microtubules, which disperses recycling endosomes and the Golgi apparatus within the cytoplasm, suggesting a specific interaction with the inclusion membrane. Consistent with this, GFP-Rab11 colocalizes with C. trachomatis IncG at the inclusion membrane. Therefore, chlamydiae recruit key regulators of membrane trafficking to the inclusion, which may function to regulate the trafficking or fusogenic properties of the inclusion.